Kinetics and Mechanism of Osmium (VIII) Catalysed Oxidation of 2-Aminoethanol and 3-Aminopropanol by Hexacyanoferrate(III) in Alkaline medium - Gupta, Sushma; Upadhyay, S.K. (Asian Journal of Chemistry, 2010)
The kinetics of the osmium(VIII) catalysed oxidation of 2-aminoethanol and 3-aminopropanol by hexacyanoferrate(III) in alkaline medium have been studied spectrophotometrically. The reaction is first order each in oxidant, alkali and catalyst. The effect of substrate on rate of reaction is negligible in each case. A retarding effect of hexacyanoferrate(II) on the rate of reaction is observed. A suitable mechanism has been proposed for the oxidation process.